Cognizing Coexistence: Perceptions and their Synthetic Unity in Kant’s 3rd Analogy - Andrew Werner (Journal of Modern Philosophy)
In the 3rd Analogy, Kant claims that I can perceive that things coexist by synthesizing my perceptions in an order-indifferent way. Reigning orthodoxy holds that I first successively perceive different things, and then (through some further act) determine that the things I perceive coexist. Focusing on prominent examples of this approach, I argue that these accounts fail to do justice to the order-indifferent synthesis that Kant describes: Strawson explains the synthesis in a way which renders Kant’s argument in the 3rd Analogy obviously unconvincing, Watkins makes the synthesis irrelevant to Kant’s argument, while Longuenesse and Allison make the unity of the synthesis obscure. The problems with these views, I contend, show that Kant thinks the rule for synthesizing my perceptions is already operative in the successive perceptions, such that the fundamental act of perception already involves ‘objective time-determinations.’ This connects with the recent dispute about whether Kant is a conceptualist: my argument provides additional evidence that Kant is a conceptualist, while also extending the conceptualist reading to the 3rd Analogy in a novel way. For those who think conceptualism is wrong, my argument serves as a critical notice that non-conceptualists have yet to offer a satisfying interpretation of the 3rd Analogy.